Analysis Of Consumer Preferences To Local Aglaonema In Deli Serdang District - Jopianus Tumanggor; Iskandarini Iskandarini; Rahmanta Rahmanta (JASc (Journal of Agribusiness Sciences), 2021)
The trend of ornamental plants during the Covid-19 pandemic has led to high public demand, especially for imported Aglaonema types because they are considered to have striking colors and patterns that are more attractive than local Aglaonema. Knowledge of consumer preferences or tastes is one of the solutions in developing local Aglaonema products so that they are not less competitive. This study aims to analyze consumer preferences for local aglaonema seen from the relative importance of attributes and the combination of attributes that consumers prefer the most. The location of the research was determined purposively, namely in Deli Serdang district. Determination of the sample is done by purposive sampling with 100 respondents. The types of data used in this study are primary data and secondary data. The analysis uses conjoint analysis. The results showed that the level of consumer interest in local aglaonema attributes ranging from the highest to the lowest was the attribute price, leaf color, leaf shape, leaf motif, plant appearance, leaf texture, and leaf size. Meanwhile, the combination of attributes that consumers like the most is a combination of red and green leaf color, lanceolate leaf shape, batik leaf motif, small leaf size, thick leaf texture, compact leaf arrangement and low price.